2021
DOI: 10.3389/fimmu.2021.602122
|View full text |Cite
|
Sign up to set email alerts
|

Lymphatic Endothelial Cell Activation and Dendritic Cell Transmigration Is Modified by Genetic Deletion of Clever-1

Abstract: Clever-1 also known as Stabilin-1 and FEEL-1 is a scavenger molecule expressed on a subpopulation of anti-inflammatory macrophages and lymphatic endothelial cells (LECs). However, its role in regulating dendritic cell (DC) trafficking and subsequent effects on immunity have remained unexplored. In this study, we demonstrate that DC trafficking from the skin into the draining lymph nodes is compromised in the absence of Clever-1. By adoptive transfer approaches we further show that the poor trafficking is due t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…More recently, also the LEC‐expressed adhesion molecule CLEVER‐1 (also known as Stabilin‐1 and FEEL‐1) was shown to impact both DC cell migration from the skin to the dLN as well as the maturation state of migrated DCs and their ability to induce T cell proliferation. 96 In further support of these findings, other studies have reported that migratory DCs present in dLNs in steady‐state generally have a less immune‐activating phenotype in comparison to LN‐resident DCs. 97 , 98 By contrast, under inflammatory conditions migratory DCs reportedly acquire a more stimulatory phenotype compared to LN‐resident DCs and are critical for inducing effective adaptive responses in the context of peripheral infection or vaccination.…”
Section: Insights Into Lymphatic Migration Gained From Microscopymentioning
confidence: 56%
See 1 more Smart Citation
“…More recently, also the LEC‐expressed adhesion molecule CLEVER‐1 (also known as Stabilin‐1 and FEEL‐1) was shown to impact both DC cell migration from the skin to the dLN as well as the maturation state of migrated DCs and their ability to induce T cell proliferation. 96 In further support of these findings, other studies have reported that migratory DCs present in dLNs in steady‐state generally have a less immune‐activating phenotype in comparison to LN‐resident DCs. 97 , 98 By contrast, under inflammatory conditions migratory DCs reportedly acquire a more stimulatory phenotype compared to LN‐resident DCs and are critical for inducing effective adaptive responses in the context of peripheral infection or vaccination.…”
Section: Insights Into Lymphatic Migration Gained From Microscopymentioning
confidence: 56%
“…Other studies identified prostaglandins secreted by LECs 94 and CD73 expressed on LECs 95 as negative modulators of DC maturation, dampening inflammation and immune responses in dLNs. More recently, also the LEC‐expressed adhesion molecule CLEVER‐1 (also known as Stabilin‐1 and FEEL‐1) was shown to impact both DC cell migration from the skin to the dLN as well as the maturation state of migrated DCs and their ability to induce T cell proliferation 96 . In further support of these findings, other studies have reported that migratory DCs present in dLNs in steady‐state generally have a less immune‐activating phenotype in comparison to LN‐resident DCs 97,98 .…”
Section: Insights Into Lymphatic Migration Gained From Microscopymentioning
confidence: 99%
“…So far, only few molecular interactions that mediate this effect have been identified: For example, the LEC-expressed adhesion molecule CLEVER-1 was not only shown to impact DC and T cell migration to dLNs, but also to suppress expression of costimulatory molecules in DCs. In absence of CLEVER-1, higher antigen-specific proliferative responses of T cells were observed in dLNs [137]. Similarly, another study identified LEC-derived prostaglandins as negative modulators of DC maturation [177].…”
Section: Beyond Transport: Emerging Roles Of Afferent Lymphatics In Immune-modulationmentioning
confidence: 91%
“…Blockade of CLEVER-1 significantly decreased skin egress of CD4 + and CD8 + T cell to the dLN in vivo [171,172]. Interestingly, CLEVER-1 was recently also found to mediate DC migration to dLNs [137].…”
Section: Adhesion Moleculesmentioning
confidence: 96%
“…LECs of the LNs can efficiently scavenge and present peripheral antigens on MHCI to induce tolerance by specific deletion of autoreactive CD8 + T cells, and phagocytose and process exogenous antigen and cross-present it to naïve CD8 + T cells. Moreover, DCs migrating to the draining LNs within Clever-1-positive lymphatics experience immunosuppressive interaction with LECs [105]. Early atherosclerotic plaque formation is associated to collecting lymphatic dysfunction to propel lymph forward in a nonspecific cholesterol-but LDL-cholesterol receptor (LDLR)dependent manner [106].…”
Section: Cardiac Lymphatics Respond To MI By Re-activating Genementioning
confidence: 99%